Breakthrough of contaminant plumes in saturated volcanic rock: implications from the Yucca Mountain site. Issue 3 (18th April 2013) - Kelkar, S.; Srinivasan, G.; Robinson, B. A.; Roback, R.; Viswanathan, H.; Rehfeldt, K.; Tucci, P.
Abstract: This manuscript addresses the topic of transverse dispersion and its impact on the behavior of the saturated zone below Yucca Mountain, a site that had been proposed for a US nuclear waste repository. Guided by a review of relevant observations of dispersion in similar formations, this study evaluates the importance of uncertainty in dispersion, particularly dispersion transverse to the mean transport direction, on metrics of interest to the Yucca Mountain risk assessment. Although as expected, larger values of transverse dispersivity lead to greater spreading of the plume in directions orthogonal to the mean flow direction, a corresponding sensitivity is not observed to the travel time statistics of the breakthrough curve at the compliance boundary. Thus, when a risk assessment is based on contaminant mass flux at compliance well or 'fence line' downstream from the source, as in the Yucca Mountain case, transverse dispersion may be of secondary importance to other parameters that more directly impact travel times. This result is in contrast to systems in which reactive transport processes are important to the attenuation of the plume, in which case transverse dispersion and mixing may be expected to play a dominant role in controlling the reaction rates and contaminant concentrations in the plume. Abstract : Contaminant plumes with significant lateral spreading indicating transverse dispersion have been reported in the literature from many sites. At the Yucca Mountain site modeling shows that changing the value of transverse dispersivity from 0.05 to 10 m lead to wider plumes, but the effect was moderate with the length to width ratio changing from 12 to 25, and the median breakthrough time at 18 km downstream from the source changing from 980 to 3000 years.